Constitutional Courts and Legislatures: Institutional Terms of Engagement - Mattias Kumm (Católica Law Review, 2017)
The debate about the legitimacy of judicial review has arguably been misframed. The question is not whether judicial review can be justified, but how judicial institutions need to be designed and how the relationship between the judicial and the legislative branches must be structured in order for it to be legitimate. After briefly describing the point of judicial review and introducing a normative standard for its legitimate institutionalization, the article analyzes a number of variables that, taken together, determine whether or not such standard is met. A third part briefly illustrates the usefulness of the established framework by analyzing and assessing the institutionalization of judicial review in the US and in the UK. As will become clear, both are problematic outlier cases: In the US the institutional position of the Supreme Court is too strong in its relationship the legislature, effectively enabling juristocracy. In the UK the position of the courts is too weak, effectively enabling electoral authoritarianism. – – O debate sobre a legitimidade da justiça constitucional tem sido porventura mal colocado. A quest\~ao n\~ao é a de saber se é possível legitimar a justiça constitucional, mas a de como arquitetar as instituiç\~oes judiciais e como estruturar as relaç\~oes entre os poderes judicial e legislativo de forma a assegurar essa legitimidade. Após uma breve referência ao valor da justiça constitucional e articulaç\~ao de um parâmetro normativo para sua institucionalizaç\~ao legítima, o artigo percorre um conjunto de variáveis que determinam a observância ou n\~ao desse parâmetro. A terceira parte ilustra sucintamente a utilidade deste modelo através da análise e do exame da institucionalizaç\~ao da justiça constitucional nos Estados Unidos e no Reino Unido. Como se tornará claro no decurso dessa análise, ambos consubstanciam casos peculiares e problemáticos: nos Estados Unidos a posiç\~ao institucional do Supremo Tribunal é demasiado forte na sua relaç\~ao com o poder legislativo, o que permite a implantaç\~ao de uma juristocracia. No Reino Unido a posiç\~ao dos tribunais é demasiado débil, o que permite a implantaç\~ao de um autoritarismo eleitoral.
Keywords: 300; judicial review; democratic legitimacy; authorial and editorial role of citizens; institutional design; strong and weak review; United States and United Kingdom; justiça constitucional; legitimidade democrática; funç\~ao autoral e editorial dos cidad\~aos; arquitetura institucional; controlo judicial forte e débil; Estados Unidos e Reino Unido